Magnitude of Needlestick and Sharp Injury and Its Associated Factors Among Nurses Working at Health Institutions in Western Ethiopia, 2020 - Abadiga M; Mosisa G; Abate Y (Dove Medical Press, 2020)
Muktar Abadiga,1 Getu Mosisa,1 Yonas Abate2 1School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 2Oromia Regional Health Bureau, Nekemte Health Center, Nekemte Town, EthiopiaCorrespondence: Muktar Abadiga Abawaji, Po. Box: 395, Nekemte Email muktarabadiga@gmail.comBackground: Needlestick and sharp injury represent a major occupational hazard in the healthcare environment with nurses experiencing a large proportion of the burden. It is a potential for transmission of bloodborne pathogens including the human immunodeficiency virus, hepatitis B and C virus. Needlestick and sharp injuries are neglected and are often not reported. Few studies have been conducted in Ethiopia, and no study was conducted particularly in the Western part of a country. Therefore, this study aimed to assess needlestick and sharp injuries and associated factors among nurses working at health institutions in western Ethiopia, 2020.Methods: An institutional based cross-sectional study was conducted on 297 nurses, from January 15 to 30, 2020. The study participants were selected by a simple random sampling method and data were collected using a self-administered questionnaire. Multivariable logistic regression was used to identify associated factors of needlestick and sharp injury. The association between needle stick and sharp injury and associated factors were measured using the odds ratio at a 95% confidence interval. The statistical significance was made at a p-value of less than 0.05.Results: Out of 297 nurses who participated in the study, 100 (33.7%) had encountered needlestick and sharp injury in the past 12 months. Recapping the needle (AOR=3.99 95% CI: 2.20, 7.21), non-utilization of infection prevention guideline (AOR= 2.69, 95% CI: 1.29, 5.60), not taking injection safety training (AOR = 2.25, 95% CI: 1.22, 4.13) and having job-related stress (AOR= 1.93, 95% CI: 1.10, 3.41) were significantly associated with the needlestick and sharp injury.Conclusion: In this study, the magnitude of needlestick and the sharp injury was high. The nurse should not recap the needles, should utilize infection prevention guidelines, should minimize stress, and routine injection safety training should be given to minimize needlestick and sharp injuries.Keywords: needlestick and sharp injury, associated factors, nurses, western Ethiopia